GAMBARAN PROKRASTINASI AKADEMIK SISWA SMP DI DAERAH PESISIR SURABAYA - Rahmania, Andi Maulida; Budi, Widjajaning; Utami, Dessy Nur (Jurnal Psikologi : Media Ilmiah Psikologi, 2021)
AbstractAcademic procrastination can cause several disadvantages to students. One of the effects of academic procrastination on students is the decrease of student performance. This study aims to determine academic procrastination os Surabaya coastal students. This study involved 194 private junior high school students un coastal area of Surabaya. Measurement in this study was using the academic procrastination scale compiled by researchers based on Ferraro’s theory. The academic procrastination scale has 15 valid items and the Cronbach alpha coefficient of the scale is 0.848. Data Analiysis was performed using descriptive statistical techniques. The result showed that most of the coastall students showed moderate academic procrastination. The aspect of academic procrastination that arose the most from the respondents were the aspect of delaying starting to work on assignments and doing other activities while doing the task.  Keywords:  Academic Procrastination, Coastal Students Abstrak Prokrastinasi akademik dapat menimbulkan beberapa kerugian pada siswa. Salah satu dampak prokrastinasi akademik pada siswa adalah menurunnya performa akademik siswa. Penelitian ini bertujuan untuk mengetahui prokrastinasi akademik siswa pesisir Surabaya. Penelitian ini melibatkan 194 siswa SMP swasta di daerah pesisir Surabaya. Pengukuran dilakukan menggunakan skala prokrastinasi akademik yang disusun oleh peneliti berdasarkan teori dari Ferrari. Skala prokrastinasi akademik memiliki 15 aitem valid dengan nilai koefisien cronbach alpha sebesar 0,848. Analisis data dilakukan dengan menggunakan teknik statistik deskriptif. Hasil penelitian menunjukkan bahwa sebagian besar siswa pesisir menunjukkan prokrastinasi akademik dalam kategori sedang. Aspek prokrastinasi akademik yang paling banyak muncul dari responden adalah aspek menunda memulai mengerjakan tugas dan melakukan aktivitas lain dalam pengerjaan tugas. Kata Kunci: Prokrastinasi Akademik, Siswa Pesisir